Factors Affecting Compliance of Infection Control Measures among Dental Radiographers - Maram Alakhras; Dana S. Al-Mousa; Arwa Mahasneh; Amani G. AlSa’di (International Journal of Dentistry)
Objectives. To assess the level of dental radiographers’ compliance with infection control measures and to evaluate the factors affecting their compliance. Methods. The study included 175 dental radiographers. Compliance with infection control was evaluated with a self-administered questionnaire consisting of 33 questions related to vaccination, hand hygiene (HH), personal protective equipment (PPE), disinfection and sterilization, and use of surface barriers. Pearson’s chi-square test was used to compare compliance between subgroups of radiographers. Results. 64.6% of participants were females, and 62.9% was younger than 30 years. 13.0% of the sample population had >10 years of experience and 28.0% take radiographs for >20 patients/day. 66.9% of participants wash their hands before/after taking radiographs. 26.3% of participants had vaccination against hepatitis B, tetanus, and tuberculosis. 12.6% fully use PPE, 10.9% perform complete disinfection and sterilization, and 16.0% apply all kinds of surfaces barriers. Vaccination was significantly affected by age, gender, and practice type. HH was affected by years of experience and number of patients radiographed per day. PPE was influenced by number of hours worked per week and patients radiographed daily. Disinfection and sterilization was affected by practice type and years of experience. The use of surface barriers was affected by age, practice type, and number of patients radiographed/day. Conclusions. The current study indicated poor compliance with infection control practices among dental radiographers. We recommend continuing educational programs and training courses to increase dental radiographers’ awareness of local and international infection control guidelines and to enhance their implementation of these guidelines.